Phenomenology of spouse selection of young women in Mashhad - Ahmadreza Asgharpour Masouleh; Mahdi Kermani; Zahra Baradaran Kashani (زن در فرهنگ و هنر, 2017)
In each community, there are certain criteria and norms for selection of a spouse according to the conditions and requirements of society. In other words, selection of a spouse is a social affair, greatly influenced by the dominant values of society. More researches in this area have used deductive strategies and quantitative methods to investigate the phenomenon. However, this phenomenon has subjective dimensions and diverse objective manifestations in life experience of social actors that are complex at the same time. This research is based on a phenomenological approach to explore the meaning of choosing a spouse among young women as a social phenomenon. This phenomenological study was carried out with the participation of fifteen young girls married in the city of Mashhad who were chosen purposefully. The results showed that there are three dominant patterns for the selection of a spouse: style based on traditional patterns, style based on friendly interactions, intermediate style (friendly interactions under the supervision of family). Also the criteria making, control of criteria, adaptation, acceptance and final selection represent the original dimensions of spouse selection common in life experience of participants under study.